Independent effects of the chemical and microstructural surface properties of polymer/ceramic composites on proliferation and osteogenic differentiation of human MSCs. (15th September 2016) - Sun, Lanying; Danoux, Charlène B.; Wang, Qibao; Pereira, Daniel; Barata, David; Zhang, Jingwei; LaPointe, Vanessa; Truckenmüller, Roman; Bao, Chongyun; Xu, Xin; Habibovic, Pamela
Graphical abstract: Abstract: Within the general aim of finding affordable and sustainable regenerative solutions for damaged and diseased tissues and organs, significant efforts have been invested in developing synthetic alternatives to natural bone grafts, such as autografts. Calcium phosphate (CaP) ceramics are among widely used synthetic bone graft substitutes, but their mechanical properties and bone regenerative capacity are still outperformed by their natural counterparts. In order to improve the existing synthetic bone graft substitutes, it is imperative to understand the effects of their individual properties on a biological response, and to find a way to combine the desired properties into new, improved functional biomaterials. To this end, we studied the independent effects of the chemical composition and surface microstructure of a poly(lactic acid)/hydroxyapatite (PLA/HA) composite material on the proliferation and osteogenic differentiation of clinically relevant bone marrow-derived human mesenchymal stromal cells (hMSCs). While the molecular weight of the polymer and presence/absence of the ceramic phase were used as the chemical variables, a soft embossing technique was used to pattern the surfaces of all materials with either pits or pillars with identical microscale dimensions. The results indicated that, while cell morphology was affected by both the presence and availability of HA and by the surface microstructure, the effect of the latter parameter on cell proliferation was negligible. The osteogenic differentiation of hMSCs, and in particular the expression of bone morphogenetic protein 2 ( BMP-2 ) and osteopontin ( OP ) were significantly enhanced when cells were cultured on the composite based on low-molecular-weight PLA, as compared to the high-molecular-weight PLA-based composite and the two pure polymers. The OP expression on the low-molecular-weight PLA-based composite was further enhanced when the surface was patterned with pits. Taken together, within this experimental set up, the individual effect of the chemistry, and in particular of the presence of CaP, was more pronounced than the individual effect of the surface microstructure, although their combined effects were, in some cases, synergistic. The approach presented here opens new routes to study the interactions of biomaterials with the biological environment in greater depths, which can serve as a starting point for developing biomaterials with improved bioactivity. Statement of Significance: The aim of the this study was to obtain insight into independent effects of the chemical composition and surface microstructure of a poly(lactic acid)/hydroxyapatite (PLA/HA) composite material on the morphology, proliferation and osteogenic differentiation of clinically relevant bone marrow-derived human mesenchymal stromal cells (hMSCs). While the need for synthetic alternatives for natural bone in bone regenerative strategies is rapidly increasing, the clinical performance of synthetic biomaterials needs to be further improved. To do this successfully, we believe that a better understanding of the relationship between a property of a material and a biological response is imperative. This study is a step forward in this direction, and we are therefore convinced that it will be of interest to the readers of Acta Biomaterialia .